PENGARUH PENDEKATAN JOYFUL LEARNING TERHADAP HASIL BELAJAR SISWA - Wijaya, Adi Atma; Yusni Arni; Susanti Faipri Selegi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Joyful Learning approach on the learning outcomes of fifth-grade students at SD Negeri 93 Palembang in mathematics. This research is of a quantitative type using the quasi-experimental method with a Nonequivalent Control Group Design. The population of this study consists of all fifth-grade students at SD Negeri 93 Palembang. The sample of this study consists of students from class VC as the experimental class and class VB as the control class, totaling 61 students. The sampling technique used is Simple Random Sampling. The data collection techniques in this study are tests and documentation. The results of this study indicate a significant effect in the experimental class with an average learning outcome score of 43.83 in the pretest and 80.5 in the posttest, while the control class had a pretest score of 34.03 and a posttest score of 52.41. The results of the t-test calculation showed a significant value (2-tailed) = 0.000 < 0.05, thus Ho is rejected and Ha is accepted. Thus, there is an influence of the Joyful Learning approach on students' learning outcomes. so it can become one of the solutions to improve student learning outcomes at SD Negeri 93 Palembang.